Corneal application of SOCS1/3 peptides for the treatment of eye diseases mediated by inflammation and oxidative stress - Ahmed, Chulbul M.; Johnson, Howard M.; Lewin, Alfred S. (Frontiers in Immunology, 2024)
Several blinding diseases affecting the retina and optic nerve are exacerbated by or caused by dysregulated inflammation and oxidative stress. These diseases include uveitis, age related macular degeneration, diabetic retinopathy and glaucoma. Consequently, despite their divergent symptoms, treatments that reduce oxidative stress and suppress inflammation may be therapeutic. The production of inflammatory cytokines and their activities are regulated by a class of proteins termed Suppressors of Cytokine Signaling (SOCS). SOCS1 and SOCS3 are known to dampen signaling via pathways employing Janus kinases and signal transducer and activator of transcription proteins (JAK/STAT), Toll-like Receptors (TLR), nuclear factor kappa-light-chain-enhancer of activated B (NF-κB), mitogen activated kinase (MAPK) and NLR family pyrin domain containing 3 (NLRP3). We have developed cell-penetrating peptides from the kinase inhibitory region of the SOCS1 and SOCS3 (denoted as R9-SOCS1-KIR and R9-SOCS3-KIR) and tested them in retinal pigment epithelium (RPE) cells and in macrophage cell lines. SOCS-KIR peptides exhibited anti-inflammatory, anti-oxidant and anti-angiogenic properties. In cell culture, both Th1 and Th17 cells were suppressed together with the inhibition of other inflammatory markers. We also observed a decrease in oxidants and a simultaneous rise in neuroprotective and anti-oxidant effectors. In addition, treatment prevented the loss of gap junction proteins and the ensuing drop in transepithelial electrical resistance in RPE cells. When tested in mouse models by eye drop instillation, they showed protection against autoimmune uveitis, as a prophylactic as well as a therapeutic. Mice with endotoxin-induced uveitis were protected by eye drop administration as well. R9-SOCS3-KIR was particularly effective against the pathways acting through STAT3, e.g. IL-6 and VEGF-A mediated responses that lead to macular degeneration. Eye drop administration of R9-SOCS3-KIR stimulated production of antioxidant effectors and reduced clinical symptoms in mouse model of oxidative stress that replicates the RPE injury occurring in AMD. Because these peptides suppress multiple pathogenic stimuli and because they can be delivered topically to the cornea, they are attractive candidates for therapeutics for uveitis, macular degeneration, diabetic retinopathy and glaucoma.